STATUS GIZI REMAJA DI SMKN 1 INDRAMAYU KABUPATEN INDRAMAYU - Siti Nurbaeti, Tayong (Abdi Wiralodra : Jurnal Pengabdian Kepada Masyarakat, 2019)
Nutrition is defined as a process of organisms using food consumed normally through the process of digestion, absorption, transportation, storage, metabolism and expenditure of nutrients to maintain the life, growth and normal functioning of organs and to produce energy. Adolescence is very important because it is a transitional period between children and adults. Balanced Nutrition at this time will greatly determine their maturity in the future. This community service was conducted at SMK Negeri 1 Indramayu with the aim of knowing the description of adolescent nutritional status by measuring the knowledge and consumption patterns of adolescents. The results of community service showed that most (45%) of adolescent nutrition knowledge was quite good, most (65%) of teenage consumption patterns were lacking and most (75%) nutritional status of normal adolescents.